What factors affect the effectiveness of long - term analgesic therapy for osteoarthritis? Data analysis of the multi - center 3-month PARACELSUS study - A E Karateev; A M Lila; E Yu Pogozheva; V N Amirdzhanova; E S Filatova (Терапевтический архив, 2019)
There are factors that can affect the effectiveness of treatment of osteoarthritis (OA). Aim to identify factors affecting the effectiveness of long - term analgesic therapy in OA. Materials and methods. The study included 6448 patients (70.9% female and 29.1% male), middle age 57.8±10.2 years, with severe pain [≥40 mm on the visual analog scale]. All patients received the preparation of avocado - soybean unsaponifiables (ASU) 300 mg/day. For pain relief at the beginning and during the study, the drug Ketoprofen lysine salt (KLS) 320 mg/day was used. The efficiency criterion was pain reduction ≥50% and satisfaction with treatment ≥4 on a 5-point scale. The influence of a number of factors on the result of treatment was evaluated. Results. For 3 months of treatment, the pain decreased from 63.7±12.0 to 14.2±11.7 mm VAS. The result was evaluated as "good" or "excellent" 81.7% of patients. Adverse reactions were rare. In total, a good response to therapy was noted in 87.4% of patients. Gender, body mass index ≥30 kg/m2, type 2 diabetes mellitus, poor effect of non - steroidal anti - inflammatory drugs (NSAIDs) and Symptomatic Slow-Acting Drugs in Osteoarthritis (SYSADOA) in history did not affect the result. The effect was lower in persons >65 years [odds ratio (OR) 0.418; 95% confidence interval (CI) 0.342-0.509, p2 by Kellgren-Lawrence (OR 0.556; 95% CI 0.298-0.738, p